Calasiris the Pseudo-Greek Hero: Odyssean Allusions in Heliodorus' Aethiopica - Bartley, Christina Marie (Université d'Ottawa / University of Ottawa, 2021)
This thesis seeks to analyze the Homeric allusions in the Aethiopica with an inclusive definition to explore Heliodorus’ authorial motives. To approach this project, I use textual analysis to avoid arguments rooted in assumptions of the historical context of the novel, about which we know almost nothing. I explore how links to Homer’s Odyssey are visible within the structural organization of the text and the content of the text. I also explore how the content of the novel reproduces actions and compatible settings of Odyssean characters, which therefore qualifies Heliodorus’ characters in a metaliterary commentary with Homer’s archaic epic poem. The division of Odyssean actions and traits depicted in Heliodorus’ characters introduce a new addition to the heroic legacy established by Homer and distances the hero from Greek identity. I conclude that Heliodorus’ adherences to epic conventions and departures thereof inform the subtextual commentaries conveyed in the Aethiopica.
Keywords: Aethiopica; Heliodorus; Ancient Greek Novel; Allusions; Intertextuality; Homer; Metaliterary commentary; Calasiris; Odysseus; Odyssey; Iliad; Episodes